Improving Emergency Fire Drill Skills and Capability to Deal with Fire Emergencies on the MV. Pacific Bulk - Muhammad Dany Firmansah; Anak Agung Istri Sri Wahyuni; Otri Wani Sihaloho; Arleiny (International Journal of Science and Environment (IJSE), 2026)
Ship fires pose a high risk to crew safety, necessitating increased emergency fire drill competency. This study analyzes crew preparedness and skill enhancement strategies during emergency fire drills on board the MV Pacific Bulk. Using a descriptive qualitative approach, a purposive sampling of 25 crew members involved key officers (Chief Officer, Officer on Duty, Bosun and A/B) was conducted through in-depth interviews, participant observation, and documentation analysis. Data analysis followed the Miles and Huberman model: data reduction, presentation, and verification through triangulation. Results showed good procedural compliance, a 5-minute alarm response, full equipment readiness, and effective coordination during the galley fire simulation. Routine drills, safety meetings, and familiarization of new crew members proved successful, although scenario variations need to be improved. In conclusion, the MV Pacific Bulk has solid emergency preparedness in accordance with SOLAS standards, with various drill scenarios recommended for optimal crew competency.